Effect of N-[(imino(arylamino)methyl]-N-2-pyridyl aminocarbothioamide hydrochlorides on blood glucose and cholesterol levels of albino rats - Pandeya S.N.; Srivastava V.; Chaubey M. (My University, 2025)
[No abstract available]